แนวทางการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4 ของสถานศึกษา สังกัดสำนักงานเขตพื้นที่ประถมศึกษาร้อยเอ็ด เขต 2 - เนตรวงศ์, จันทร์หอม; ลดาวัลย์, กฤตยากร (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 3 (2567): กันยายน-ธันวาคม 2567, 2023)
การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาระดับการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4 ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 2) เพื่อเปรียบเทียบระดับการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4 ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 จำแนกตามตำแหน่ง ระดับการศึกษาและประสบการณ์การทำงาน 3) เพื่อศึกษาแนวทางการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4 ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 กลุ่มตัวอย่าง ได้แก่ ครูบุคลากรทางการศึกษา จำนวน 214 คน เครื่องมือวิจัยเป็นแบบสอบถามมาตราส่วน 5 ระดับ มีค่า IOC ระหว่าง 0.67-1.00 มีค่าความเที่ยงเท่ากับ 0.89 สถิติที่ใช้ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน t-test และการวิเคราะห์ความแปรปรวนทางเดียวของการทดสอบค่า F-test (One-Way ANOVA) ผลการวิจัยพบว่า 1) แนวทางการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 โดยรวมอยู่ระดับมาก ที่ค่าเฉลี่ยสูงสุดไปหาต่ำสุด ได้แก่ การรู้จักนักเรียนเป็นรายบุคคล รองลงมาคือ การคัดกรองนักเรียน การส่งต่อ การส่งเสริมและพัฒนานักเรียน ส่วนที่ค่าเฉลี่ยต่ำสุด คือ การป้องกันช่วยเหลือและแก้ไข 2) การเปรียบเทียบระดับความคิดเห็นที่มีต่อแนวทางการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4 ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2  จำแนกตามตำแหน่ง การคัดกรองนักเรียน แตกต่างอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 นอกนั้นไม่แตกต่าง จำแนกตามระดับการศึกษา การป้องกันช่วยเหลือและแก้ไข และการส่งต่อ ไม่แตกต่าง นอกนั้นแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 จำแนกตามประสบการณ์ทำงาน ไม่แตกต่าง 3) แนวทางการบริหารระบบดูแลช่วยเหลือนักเรียนตามหลักสังคหวัตถุ 4 ของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 ได้จากการสัมภาษณ์ พบว่า ผู้บริหาร ครู ช่วยเหลือนักเรียนตามขั้นตอน แบ่งกลุ่มปกติ กลุ่มเสี่ยง กลุ่มมีปัญหา รู้จักนักเรียนรายบุคคล คัดกรอง ส่งเสริมพัฒนา การป้องกันแก้ไขปัญหาและส่งต่อ This research has the following objectives: 1) To study the administrative level of the student care and assistance system according to the principles of Sanghawatthu 4 of educational institutions under the Roi Et Primary Educational Service Area Office 2. 2) To compare the level of administration of the student support system according to the principles of Sanghawatthu 4 of educational institutions under the Roi Et Primary Educational Service Area Office, Area 2, classified by position. Education level and work experience 3) To study the guidelines for the administration of the student support system according to the principles of Sanghawatthu 4 of educational institutions under the Roi Et Primary Educational Service Area Office, Area 2. The sample group included 214 teachers and educational personnel. The research instrument was a 5-point scale questionnaire with an IOC between 0.67-1.00 and a reliability of 0.89. Statistics used included frequency, percentage, mean, standard deviation, t-test, and analysis of reliability. One-way variance of the F-test (One-Way ANOVA) The research results showed that: 1) Guidelines for the administration of the student support system according to Sanghawatthu principles 4 of the educational institutions under the Roi Et Primary Educational Service Area Office, Area 2 Overall it is at a high level. The highest to lowest average is knowing students individually, followed by student screening. Forwarding Student promotion and development The lowest average part It is prevention, help and correction. 2) Comparison of the level of opinions towards the administration guidelines for student care and support systems according to the principles of Sanghawatthu 4 of educational institutions under the Roi Et Primary Educational Service Area Office 2 Classified by position Student screening They are significantly different at the .05 level, otherwise they are not different. Classified by educational level Prevention, assistance and correction, and referrals are not different. Other than that, they are significantly different at the .05 level. Classified by work experience are not different. 3) Guidelines for managing the student care system according to the principles of Sanghawatthu 4 of educational institutions under the Roi Et Primary Educational Service Area Office, Area 2. From interviews, it was found that administrators and teachers help students according to the steps. Divide into normal groups, risk groups, problem groups, get to know individual students, screen, promote development. Prevention, problem solving and forwarding